STRUCTURING THE PROFESSIONAL SKILLS SYSTEM SELF-ORGANIZATIONS OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the question of classification of skills of professional self-organizing and their role in professional becoming of the future teachers.